Advances in immune therapies in hematological malignancies. (8th October 2021) - Mazzarella, Luca; Enblad, Gunilla; Olweus, Johanna; Malmberg, Karl‐Johan; Jerkeman, Mats
Abstract: Immunotherapy in cancer takes advantage of the exquisite specificity, potency, and flexibility of the immune system to eliminate alien tumor cells. It involves strategies to activate the entire immune defense, by unlocking mechanisms developed by tumor cells to escape from surrounding immune cells, as well as engineered antibody and cellular therapies. What is important to note is that these are therapeutics with curative potential. The earliest example of immune therapy is allogeneic stem cell transplantation, introduced in 1957, which is still an important modality in hematology, most notably in myeloid malignancies. In this review, we discuss developmental trends of immunotherapy in hematological malignancies, focusing on some of the strategies that we believe will have the most impact on future clinical practice in this field. In particular, we delineate novel developments for therapies that have already been introduced into the clinic, such as immune checkpoint inhibition and chimeric antigen receptor T‐cell therapies. Finally, we discuss the therapeutic potential of emerging strategies based on T‐cell receptors and adoptive transfer of allogeneic natural killer cells. Abstract :